2020
DOI: 10.1007/s12182-019-00418-9
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of magnetic field and nanocomposite pour point depressant on the yield stress of waxy model oil

Abstract: Yield stress, as the key parameter to characterize the network strength of waxy oil, is important to the petroleum pipeline safety. Reducing the yield stress of waxy oil is of great significance for flow assurance. In this study, the effect of alternating magnetic field (intensity, frequency) on the yield stress of a waxy model oil with nanocomposite pour point depressant (NPPD) is systematically investigated. An optimum magnetic field intensity and frequency is found for the reduction in yield stress. When ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In recent years, with the development of micro-and nanocomposite pour point depressants (discussed in detail later in this review), Huang 108 and Yu 120 and their co-workers reported that the addition of a composite pour point depressant with magnetic particles as the core to crude oil can substantially change the structure and aggregation state of precipitated wax crystals when a magnetic field is applied (Figure 13).…”
Section: Strategies For Improving the Flowability Of Waxy Oilsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, with the development of micro-and nanocomposite pour point depressants (discussed in detail later in this review), Huang 108 and Yu 120 and their co-workers reported that the addition of a composite pour point depressant with magnetic particles as the core to crude oil can substantially change the structure and aggregation state of precipitated wax crystals when a magnetic field is applied (Figure 13).…”
Section: Strategies For Improving the Flowability Of Waxy Oilsmentioning
confidence: 99%
“…A large number of experimental studies have confirmed the viscosity reduction effect in waxy crude oil after magnetic field treatment, and the viscosity reduction rate is generally above 30%. However, the experimental results obtained from different studies vary greatly in terms of the type of magnetic field, magnetic field strength, treatment time, treatment temperature, and physical and chemical properties of crude oil. The essential reason is that the mechanism of viscosity reduction by magnetization of crude oil is still controversial.…”
Section: Strategies For Improving the Flowability Of Waxy Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the precipitation of wax crystals and related deposition problems are an important flow assurance topic under low-temperature deep-water circumstances. Wax can precipitate and crystallize from the bulk oil phase and form a network-like structure, which can bring high risks in liquidity deterioration, blockage, , or rupture accidents. Adding pour point depressants is an effective method to improve the rheological behavior of waxy oil.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 51 also investigated the effect of wax on the cohesive force between hydrate particles. Since adding pour point depressants can undermine the structure of wax and improve the flow ability of crude oil, 29,30,32,52 it is a potential method to improve the rheological behavior of the wax−hydrate coexistence system. Until recently, the influence of pour point depressants on the coupling effect of wax and hydrate has rarely been investigated.…”
Section: ■ Introductionmentioning
confidence: 99%